Penerimaan Diri Korban Toxic Relationship dalam Menumbuhkan Kesehatan Mental - Ulin Nihayah; Ade Vinna Pandu Winata; Titin Yulianti (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2021)
Toxic relationship is one example of how then a problem that affects a person's relationship with his partner. This is usually indicated by a sense of competition from within the individual and the absence of cohesiveness. The purpose of this paper is to provide a better understanding of the self-acceptance of toxic victim relationships in fostering mental health, the author is also associated with a toxic victim case study entitled "An overview of acceptance of violence in early adults who are victims of dating violence", which includes an overview of how the attitudes and behavior of victims in accepting violence in dating and also the factors that influence it. The method in this research is descriptive research, where the researcher conducts an in-depth exploration of programs, processes, events, and activities of one or more people using a case study approach by finding a number of adult women who have experienced sexual experiences.